A desigualdade no “topo”: estratificação racial e o efeito da “cor” sobre os rendimentos de empregadores negros e brancos no Brasil - Santos, Neville Julio de Vilasboas e (2016)
This thesis takes the group of employers in Brazil as an object for quantitative analysis, using data from the National Household Survey. The most traditional Marxist theories ascribe to employers, due to its position in capital-labour struggle, a location in high income strata. However, prevails a income gap between white and black workers, with preponderance of the latter group in less privileged economy sectors, in occupations with high informality rate and in enterprises that typically employ fewer workers and whose stability tends to be lower. Following the recent social sciences interest to analyse the dynamics of racial inequality in higher social strata, this thesis aims to investigate the "color effect", considering other intervening variables, on black and white employers’ income. A logistic regression method follows a historical and theoretical contextualization of the problem of racial inequalities in Brazil and the presentation of the profile of employers, to analyze the racial inequalities in the composition of the employer group, showing that controlled influential variables, blacks are less likely to be part of that group. A central task in this thesis is the analysis of income inequality between black and white employers, based on a theoretical discussion of the rapport between racial inequality, class and income. A Oaxaca-Blinder decomposition model showed a significant disparity of average incomes, whereas an extension of the earlier model proposed by Juhn, Murphy and Pierce led to conclude that black-white income inequality evolves, beyond the means difference, a significant increase along the distribution, particularly on higher strata. Taking apart the striking effect of education, the conclusion is that the color effect (effect of racial discrimination) is decisive and increases along the income distribution.